Functional Characterization of SlSAHH2 in Tomato Fruit Ripening - Yang, Lu; Hu, Guojian; Li, Ning; Habib, Sidra; Huang, Wei; Li, Zhengguo (Frontiers in Plant Science, 2017)
Abstract S-adenosylhomocysteine hydrolase (SAHH) functions as an enzyme catalyzing the reversible hydrolysis of S-adenosylhomocysteine to homocysteine and adenosine. In the present work we have investigated its role in the ripening process of tomato fruit. Among the three SlSAHH genes we demonstrated that SlSAHH2 was highly accumulated during fruit ripening and strongly responded to ethylene treatment. Over-expression of SlSAHH2 enhanced SAHH enzymatic activity in tomato fruit development and ripening stages and resulted in a major phenotypic change of reduced ripening time from anthesis to breaker. Consistent with this, the content of lycopene was higher in SlSAHH2 over-expression lines than in wild-type at the same developmental stage. The expression of two ethylene inducible genes (E4 and E8) and three ethylene biosynthesis genes (SlACO1, SlACO3 and SlACS2) increased to a higher level in SlSAHH2 over-expression lines at breaker stage, and one transgenic line even produced much more ethylene than wild-type. Although inconsistency in gene expression and ethylene production existed between the two transgenic lines, the transcriptional changes of several important ripening regulators such as RIN, AP2a, TAGL1, CNR and NOR showed a consistent pattern. It was speculated that the influence of SlSAHH2 on ethylene production was downstream of the regulation of SlSAHH2 on these ripening regulator genes. The over-expressing lines displayed higher sensitivity to ethylene in both fruit and non-fruit tissues. Ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC) treatment accelerated ripening faster in SlSAHH2 over-expressing fruit than in wild-type. Additionally, seedlings of transgenic lines displayed shorter hypocotyls and roots in ethylene triple response assay. In conclusion, SlSAHH2 played an important role in tomato fruit ripening.